Gas-liquid two-phase flow in inclined pipes - Hernandez Perez, Valente (2008)
In order to understand the behaviour of two-phase flow in inclined pipes, an extensive programme of work has been undertaken using the Inclinable Facility in the laboratories of the School of Chemical, Environmental and Mining Engineering at the University of Nottingham. The test pipe (6.5 m long) could be positioned at angles between -20° downwards and vertical upwards. Two pipe diameters were used; namely 38 mm and 67 mm. The fluids used were air and water. Superficial velocities for air ranged from 0.15 to 8.9 m/s and from 0.04 m/s to 0.7 m/s for water. Time series of liquid holdup (using capacitance probes) and pressure drop (differential pressure transducer) were measured. In addition, a high speed video system was used in order to obtain image sequence of the flow under different selected conditions.